Deep sea 2003 : (FAO, 2005)
This is the first of the two-volume proceedings from "Deep Sea 2003: Conference on the Governance and Management of Deep-sea Fisheries". It includes the keynote addresses and papers presented on the Conference themes that covered: environment, ecosystem biology, habitat, diversity and oceanography; population biology and resource assessment; harvesting and conservation strategies for resource management; technology requirements; monitoring, compliance and controls; a review of existing policies and instruments; and governance and management. The general conclusions of the Conference contain the elements that must be addressed and undertaken if deep-sea fish resources are to be sustained and their habitat protected to ensure productivity and safeguard deep-sea biodiversity.